Hydrogel loaded with C-M dispersion liquid as well as preparation method and application of hydrogel

The hydrogel loaded with C-M dispersion solution solves the problem of mechanical strength reduction caused by acidification of paper cultural relics, achieves the deacidification and reinforcement effect, and avoids adverse effects on paper performance and has the function of preventing acid reflux.

CN119591945AActive Publication Date: 2025-03-11LIAONING UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411525136.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-11
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Paper cultural relics are prone to acidification during storage, resulting in reduced mechanical strength and irreversible deterioration. The prior art may affect the transparency, gloss and flexibility of the paper during deacidification treatment.

Method used

Using a hydrogel loaded with C-M dispersion, a hydrogel carrier capable of loading C-M dispersion was formed by wrapping sodium carboxymethylcellulose and nanomagnesium hydroxide in gellan gum, and adding calcium acetate, gelatin and glycerol, and a hydrogel carrier capable of loading C-M dispersion was applied to the paper surface to achieve deacidification and reinforcement.

Benefits of technology

This method can effectively shorten the contact time between the C-M dispersion and the paper, significantly improve the deacidification effect, and avoid residues on the surface of the paper, maintain the transparency, gloss and flexibility of the paper, and have a reinforcement effect to prevent acid reflux.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591945A_ABST
    Figure CN119591945A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of protection of paper cultural relics, and particularly relates to hydrogel loaded with C-M dispersion liquid as well as a preparation method and application of the hydrogel. The preparation method comprises the following steps: preparing a sodium carboxymethyl cellulose aqueous solution, and stirring the solution until the solution is clear and transparent; preparing a nano magnesium hydroxide ethanol dispersion liquid; mixing the two solutions in equal volume, and uniformly stirring to obtain a C-M dispersion liquid; taking low-acyl gellan gum, gelatin and glycerol, adding distilled water, swelling for 30 minutes, adding calcium acetate to obtain a hydrogel solution, mixing the C-M dispersion liquid and the hydrogel solution, uniformly stirring, heating in a microwave oven for 3-5 minutes until the solution is in a clear and transparent state, transferring into a mold while the solution is hot, and cooling to obtain the hydrogel loaded with the C-M dispersion liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of paper cultural relics protection, and particularly relates to a hydrogel loaded with CM dispersion liquid and a preparation method and application thereof. Background Art

[0002] Paper artifacts are an important part of the global cultural heritage, a carrier of art and cultural heritage, and carry great historical and cultural values. Long-term exposure to the environment, affected by their own properties and external environmental factors, often causes irreversible damage, which is specifically manifested as acidification, embrittlement, aging, slag, decay, mildew and other deterioration phenomena. Acidification refers to the process of accumulation of acidic substances in the preservation process, which is the main cause of paper deterioration. Under acidic conditions, the glycosidic bonds in the paper fibers break, and the fiber polymerization degree decreases, resulting in a decrease in the mechanical strength of the paper. The factors that cause the acidification of paper artifacts are as follows: First, acidic substances such as alum may be added during the papermaking process, and the raw materials themselves contain lignin, which will produce acidic substances after oxidation and hydrolysis. Second, during long-term storage, the acidification of paper will be accelerated by the influence of temperature, humidity, light, and gases such as chlorides, nitrogen oxides, and carbon oxides in the air. Third, the pigments, inks or chemical residues used in the printing, processing, and restoration processes will have an acidifying effect on paper artifacts. Take the newspapers from the early 20th century in the Ancient Book Collection Room of Liaoning University as an example. During the storage process, due to the influence of itself and various environmental factors, the paper turned yellow and became brittle, and there was a lot of debris falling off. After testing, the pH value of the collected residue fragments was 4.19, which was already at a severe acidification level. Therefore, deacidification protection of paper cultural relics is imminent.

[0003] In recent years, nanotechnology has been gradually applied to the field of deacidification. For example, Wang Heyun et al. prepared nano magnesium hydroxide and applied it to the deacidification of paper cultural relics. The deacidification effect of nano magnesium hydroxide on paper cultural relics was characterized by tensile strength and paper surface pH. The tensile strength was stable after deacidification, indicating that nano magnesium hydroxide can extend the shelf life of books, documents, and paper cultural relics. However, since nanoparticles are slightly soluble in organic solvents such as water and anhydrous ethanol, the present invention considers using natural polymer material sodium carboxymethyl cellulose to wrap nano magnesium hydroxide ethanol dispersion to obtain CM dispersion, but directly brushing the CM dispersion on the surface of paper so that it is in direct contact with the paper, although the effect of deacidification reinforcement can be achieved, after natural drying, it can be seen that the surface of the paper is covered with a film, the color is obviously whitish, the edge is curled, the thickness and quality of the paper are increased, and the gaps in the paper fibers under a 10x objective optical microscope are filled with many large and small, unevenly distributed particulate matter, which undoubtedly affects the transparency, original texture and flexibility of the paper itself. Summary of the invention

[0004] The purpose of the present invention is to provide a technical solution with good safety, which can avoid the adverse effects of CM dispersion liquid directly contacting paper on the transparency, glossiness, flexibility and other properties of paper, and can also achieve the deacidification and reinforcement of paper cultural relics. Nano magnesium hydroxide and sodium carboxymethyl cellulose are used as effective ingredients for deacidification and reinforcement, gellan gum is used as the base material of the hydrogel carrier, calcium acetate is used as a cross-linking agent to promote the hydrogel to change from a peptized state to a gelled state, gelatin and glycerol are used as water-locking agents to synergistically control the amount of water released when the hydrogel contacts the paper, and a hydrogel carrier that can load the CM dispersion liquid is prepared, and then the CM dispersion liquid is added to the hydrogel carrier according to a volume ratio of 2:8, 3:7, 4:6, and 1:1 to obtain a hydrogel loaded with the CM dispersion liquid, and the hydrogel is applied to the surface of the acidified paper.

[0005] To achieve the above object, the technical solution of the present invention is as follows: A hydrogel loaded with CM dispersion, the preparation method comprising the following steps:

[0006] 1) Preparation of CM dispersion: prepare sodium carboxymethyl cellulose aqueous solution, and stir the solution until it becomes clear and transparent; prepare nano magnesium hydroxide ethanol dispersion; mix the above two solutions in equal volumes and stir evenly;

[0007] 2) Preparation of hydrogel solution: low acyl gellan gum, gelatin and glycerol were added with distilled water, swollen for 30 min, and calcium acetate was added to obtain a hydrogel solution;

[0008] 3) Preparation of hydrogel loaded with CM dispersion: After mixing the CM dispersion and the hydrogel solution, stir evenly, heat in a microwave oven for 3-5 minutes until the solution becomes clear and transparent, transfer to a mold while hot, and use after cooling.

[0009] In the above-mentioned hydrogel loaded with CM dispersion, in step 1), the concentration of sodium carboxymethyl cellulose solution is 2-16 g / L; the concentration of nano magnesium hydroxide ethanol dispersion is 8-16 g / L.

[0010] In the above-mentioned hydrogel loaded with CM dispersion, in step 2), in the hydrogel solution, the concentration of low acyl gellan gum is 10-30 g / L, the concentration of gelatin is 5-30 g / L, the concentration of calcium acetate is 0.2-1.2 g / L, and the volume fraction of glycerol is 2.5-15%.

[0011] In the above-mentioned hydrogel loaded with CM dispersion, in step 3), the CM dispersion and the hydrogel solution are mixed at a volume ratio of 2:8, 3:7, 4:6, or 1:1.

[0012] In the above-mentioned hydrogel loaded with CM dispersion, in step 3), the heating is for 3-5 minutes at a heating temperature of 85°C.

[0013] The above-mentioned hydrogel loaded with CM dispersion is used in the deacidification and reinforcement of paper cultural relics.

[0014] The above-mentioned hydrogel loaded with CM dispersion is used for the paper cultural relics after acid regeneration.

[0015] The present invention has the following beneficial effects:

[0016] In the present invention, the hydrogel loaded with CM dispersion is applied to the surface of paper. Compared with directly brushing the CM dispersion on the surface of paper, the contact time between the CM dispersion and the paper is greatly shortened. The hydrogel loaded with CM dispersion can achieve the deacidification effect in only 5-40 minutes. After the deacidification is completed, the hydrogel loaded with CM dispersion can be completely peeled off from the surface of the paper, and there will be no residue on the surface of the paper. The hydrogel loaded with CM dispersion is highly operable. According to the morphology of the acidified sample, hydrogels loaded with CM dispersion of different sizes and shapes can be prepared. Under optical microscopy, it can be seen that after the hydrogel loaded with CM dispersion is deacidified on the paper, no large particles remain in the gaps between the paper fibers (such as Figure 2 As shown), the adverse effects of the CM dispersion on the transparency, glossiness, whiteness and other properties of the paper after the CM dispersion directly contacts the paper are avoided. In addition, the hydrogel loaded with the CM dispersion used in the present invention can achieve the effect of deacidification and reinforcement when applied to acidified paper, dry heat aging paper, and ultraviolet aging paper, and the deacidification and reinforcement effect is significantly improved compared with the deacidification and reinforcement effect of using a single component AGW, CM, and GG. Even if the acid reversion phenomenon occurs again after deacidification, it still has a significant reinforcement effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Flow chart of the preparation of hydrogels loaded with CM dispersion.

[0018] Figure 2 Micrographs of the fiber structure of each group of paper before and after deacidification treatment, where Ctrl is paper without deacidification treatment, AGW is paper treated with alum water, GG is paper treated with hydrogel alone, CM is paper treated with CM dispersion, and GG-CM is paper treated with hydrogel loaded with CM dispersion.

[0019] Figure 3 The deacidification effect of paper before and after aging under different treatment conditions.

[0020] Figure 4 A diagram showing the effect of different treatment conditions on paper reinforcement before and after aging.

[0021] Figure 5 The strengthening effect of paper after acid regeneration under different treatment conditions before and after aging. DETAILED DESCRIPTION

[0022] Example 1 Preparation of hydrogel loaded with CM dispersion

[0023] (1) Preparation of CM dispersion: 16 g of sodium carboxymethyl cellulose was placed in a beaker, 1000 ml of distilled water was added, and a sodium carboxymethyl cellulose solution with a concentration of 16 g / L was prepared. The solution was stirred until it became clear and transparent; 16 g of nano magnesium hydroxide was placed in a beaker, 1000 ml of anhydrous ethanol was added, and the solution was stirred on a magnetic stirrer for 40 min to prepare a nano magnesium hydroxide ethanol dispersion with a concentration of 16 g / L. The above two solutions were mixed in equal volumes and stirred evenly to prepare a CM dispersion with a sodium carboxymethyl cellulose concentration of 8 g / L and a nano magnesium hydroxide concentration of 8 g / L.

[0024] (2) Preparation of hydrogel solution: Take 20g of low acyl gellan gum, 20g of gelatin, and 100ml of glycerol and place them in a beaker, add 900ml of distilled water, swell for 30min, add 0.4g of calcium acetate, and prepare a hydrogel solution with a low acyl gellan gum concentration of 20g / L, a gelatin concentration of 20g / L, a calcium acetate concentration of 0.4g / L, and a glycerol volume fraction of 10%.

[0025] (3) Preparation of hydrogel loaded with CM dispersion: CM dispersion and hydrogel solution were mixed in a volume ratio of 1:1, stirred evenly, and placed in a microwave oven and heated at 85°C for 3-5 minutes until the solution became clear and transparent. The mixture was then transferred to a mold while hot and used after cooling.

[0026] Example 2 Application of hydrogel loaded with CM dispersion in deacidification and reinforcement of paper cultural relics

[0027] (1) Preparation of acidified samples: Based on the pH value of 4.19 of the acidified newspapers from the early 20th century in the ancient book collection room of Liaoning University, raw rice paper was used as the experimental paper. 0.025 mL of 4-14 g / L potassium aluminum sulfate solution was taken with a pipette and dropped onto the raw rice paper within a 1 cm × 1 cm area. The raw rice paper was saturated with water, and the solution naturally spread out. The paper was dried at room temperature to obtain an acidified sample of paper cultural relics.

[0028] (2) Preparation of dry heat aging samples: According to "Dry Heat Accelerated Aging of Paper and Paperboard" (GB / T 464-2008), raw rice paper was placed in a vacuum drying oven with the temperature set to 105°C and the time set to 72 hours to obtain paper cultural relic dry heat aging samples.

[0029] (3) Preparation of UV aging samples: Place the raw rice paper in a UV aging box at a power of 30 W for 24 h to obtain a UV aging sample of paper cultural relics.

[0030] (4) Experimental groups

[0031] Experimental settings Blank group (Ctrl): The blank group (Ctrl) represents the untreated acidified sample, dry heat aged sample and UV aged sample.

[0032] Gel alum water group (AGW): Weigh 0.5g gelatin particles and 0.15g aluminum potassium sulfate powder into a beaker, add 100ml distilled water, stir until dissolved, and prepare an aqueous solution of gelatin with a mass fraction of 0.5% gelatin and a mass fraction of 0.15% aluminum potassium sulfate. Use a clean soft brush to dip the aqueous solution of gelatin evenly on the surface of the acidified sample, dry heat aged sample and UV aged sample.

[0033] Hydrogel treatment group (GG): The hydrogel solution obtained in (2) of Example 1 was placed in a microwave oven and heated for 3-5 minutes at a heating temperature of about 85°C until the solution became clear and transparent. The solution was then transferred to a mold while hot, and demolded after cooling. The solution was then covered on the surface of the acidified sample, the dry heat aged sample, and the UV aged sample.

[0034] CM dispersion treatment group (CM): The CM dispersion obtained in Example 1 (1) was dipped into a clean soft brush and evenly applied on the surfaces of the acidified samples, dry heat aged samples and UV aged samples.

[0035] Group treated with hydrogel loaded with CM dispersion (GG-CM): The hydrogel loaded with CM dispersion obtained in (3) of Example 1 was covered on the surface of the acidified sample, the dry heat aged sample and the UV aged sample.

[0036] By comparing with the blank group and the control group (alum water group (AGW), hydrogel treatment group (GG), and CM dispersion treatment group (CM)), the experiment was conducted to determine whether the hydrogel loaded with CM dispersion had the effect of deacidification and reinforcement on paper cultural relics under the conditions of a volume ratio of 1:1 and a covering time of 30 minutes.

[0037] Use a pH meter to measure the pH of the paper sample according to GB / T 1545-2008 Determination of acidity or alkalinity of water extracts of paper, paperboard and pulping. The results are as follows: Figure 3As shown, in each group, compared with the Ctrl group, the pH of the paper samples treated with AGW did not change significantly, but the pH of the paper samples treated with GG, CM and GG-CM increased significantly, and each group showed a trend of pH(Ctrl)<pH(AGW)<pH(CM)<pH(GG)<pH(GG-CM), indicating that the deacidification effect of the hydrogel loaded with CM dispersion prepared in a volume ratio of 1:1 was better than that of the other control groups, and the pH range after deacidification was between 7.24-7.37.

[0038] The paper sample tensile force was measured using a ZQ-21A tensile testing machine. Figure 4 As shown, in each group, compared with the Ctrl group, the tensile force of the paper samples treated with GG increased slightly, while the tensile force of the paper samples treated with AGW, CM and GG-CM increased significantly, and each group showed a trend of tension (Ctrl) < tension (GG) < tension (CM) < tension (AGW) < tension (GG-CM), indicating that the hydrogel loaded with CM dispersion prepared at a volume ratio of 1:1 has better reinforcement effect than the other control groups, and the tension range after treatment is between 34.5-42.9N.

[0039] Example 3 Application of hydrogel loaded with CM dispersion to paper cultural relics after acidification

[0040] The experiment set up a blank group (Ctrl), alum water group (AGW), hydrogel treatment group (GG), CM dispersion treatment group (CM) and hydrogel treatment group loaded with CM dispersion (GG-CM). By comparing with the blank group and the control group, the volume ratio of 1:1 and the covering time of 30 minutes were tested to see whether the hydrogel loaded with CM dispersion had a reinforcing effect on the deacidified paper cultural relics after re-acidification.

[0041] The ZQ-21A tensile testing machine was used to measure the tensile strength of the paper sample after acid regeneration. Figure 5 As shown, in the acidification group and dry heat aging group, the tensile strength of the paper that was deacidified after treatment with single components AGW, GG and CM increased compared with the blank group. In the UV aging group, the tensile strength of the paper that was deacidified after treatment with AGW increased compared with the blank group, and the tensile strength of the paper that was deacidified after treatment with GG and CM showed a slightly decreasing trend compared with the blank group. However, the tensile strength of the paper that was deacidified after treatment with GG-CM in each group showed a significant increasing trend compared with the Ctrl group and other treatment groups, indicating that the hydrogel loaded with CM dispersion prepared in a volume ratio of 1:1 not only has the effect of deacidifying acidified paper, but also has a reinforcement effect even if the phenomenon of deacidification occurs during the storage process after deacidification, and the tensile strength ranges from 33.3 to 45.3N.

[0042] In summary, the hydrogel loaded with CM dispersion provided by the present invention has a significant deacidification and reinforcement effect compared with the traditional deacidification reagent alum water (AGW) and each individual component, showing that it can achieve both deacidification and reinforcement effects, and can avoid the phenomenon of film formation, thickening, hardening, brittleness and curling on the surface of paper treated with CM dispersion alone, and can improve the problem that the paper only has a single effect of deacidification or reinforcement after being treated with AGW or GG alone. Even if the paper re-acidifies after deacidification, it still has a reinforcement effect, avoiding the phenomenon of reduced mechanical strength, fiber breakage, crushing, and slag falling after the paper is acidified.

Claims

1. A hydrogel loaded with a CM dispersion, characterized in that: The preparation method comprises the following steps: 1) Preparation of CM dispersion: prepare sodium carboxymethyl cellulose aqueous solution, and stir the solution until it becomes clear and transparent; prepare nano magnesium hydroxide ethanol dispersion; mix the above two solutions in equal volumes and stir evenly; 2) Preparation of hydrogel solution: low acyl gellan gum, gelatin and glycerol were added with distilled water, swollen for 30 min, and calcium acetate was added to obtain a hydrogel solution; 3) Preparation of hydrogel loaded with CM dispersion: After mixing the CM dispersion and the hydrogel solution, stir evenly, heat in a microwave oven for 3-5 minutes until the solution becomes clear and transparent, transfer to a mold while hot, and use after cooling.

2. A hydrogel loaded with CM dispersion according to claim 1, characterized in that: In step 1), the concentration of the sodium carboxymethyl cellulose solution is 2-16 g / L; the concentration of the nano magnesium hydroxide ethanol dispersion is 8-16 g / L.

3. The hydrogel loaded with CM dispersion according to claim 1, characterized in that: In step 2), in the hydrogel solution, the concentration of low acyl gellan gum is 10-30 g / L, the concentration of gelatin is 5-30 g / L, the concentration of calcium acetate is 0.2-1.2 g / L, and the volume fraction of glycerol is 2.5-15%.

4. The hydrogel loaded with CM dispersion according to claim 1, characterized in that: In step 3), the CM dispersion and the hydrogel solution were mixed at a volume ratio of 2:8, 3:7, 4:6, or 1:

1.

5. The hydrogel loaded with CM dispersion according to claim 1, characterized in that: In step 3), the heating is performed for 3-5 minutes at a temperature of 85°C.

6. Use of the hydrogel loaded with CM dispersion according to claim 1 in deacidification and reinforcement of paper cultural relics.

7. Use of the hydrogel loaded with CM dispersion according to claim 1 in paper cultural relics after acid regeneration.

Citation Information

Patent Citations

  • Preparation method of environmentally-friendly rapid self-repairing hydrogel

    CN109749097A

  • Composition for paper deacidification, process to obtain it and method for its application

    EP2626464A1

  • Stabilized alkaline composite nanoparticles, method for producing the same and use thereof

    EP3072933A1

  • Gypsum-based composite materials reinforced by cellulose ethers

    US20040092625A1